Introduction to environmental science - Unday, Joel E.; Banzuela, Shirley O.;Dalisay, Jill B.;Aromin, Mayetter L. (Quezon City, Philippines : Maxcor Publishing House Inc., 2012)
This introduction to environmental science was prepared to meet the needs of the students in all disciplines and acquire the basic knowledge and principles relating to the general concepts of ecology, natural resources, biodiversity, population, and pollution; its sources, effects and mitigations.
Introduction : environmental science -- Ecosystem -- Energy flow in an ecosystem -- Biochemical cycles -- Population ecology -- Community ecology -- Biomes of the earth -- Philippine biodiversity -- Philippine natural resources -- Air pollution -- Greenhouse effect and global warning -- Water pollution -- Solid waste pollution -- Philippine environmental laws.
Includes bibliographical references.
Keywords: ENVIRONMENTAL SCIENCES -- TEXTBOOK